Methods and procedures for defining best silvicultural practices and management regimes for fast-growing tree plantations - Kanninen, M.; Pérez, D. (Scientific Publishers (India), 2006)
Fast grwoing tree species have been used in many tropical countries for a variety of production purposes, including timber wood (as monoculture and as mixture of various species), silvopastoril (combined with cattle), agroforestry (combined with coffee culture mainly), and with other purposes such as soil enrichment, livingfences (wind breakers), erosion mitigation, etc. Several studies have been carried out on native and excotic multipurpose species, including adaptability tests, nursery production - genetic improvement, plantation management, stand growth and yield etc. Procedures for developing and evaluating stand density indicators, competition indices, merchantable volume equations, prunning and thinning methodologies, among others, are discussed on this paper, aiming at facilitating silvicultural management tools for the intensive culture of fast growing tree species. Experiences developing management guidelines for Tectona grandis, Bombacopsis quianta, and Terminalia amazonia under different scenarios are discussed in this paper, based on several case studies carried out during the last 10 years on private farms and companies of small (10 ha) and large (3000 ha) size in different regions of Costa Rica.